(3OjhGf GdcjhGfjs - (3CHhHcQ CMeO Hf MSjf HGTG Hf eUWai Hf MSjf Hf eMeO Hf cjhGf GdTgjQ H` GdcjhGfjs; (3GdcjhGfj , CMeO Hf MSjf HGTG Hf eUWaj Hf MSjf Hf eMeO Hf cjhGf, GdcjhGfj,J (B1173 (3g` s ((3EHQGgje GdHdjSj s)
(3ChdgG (B:s
(3bGd CfLM Gddg bUOg(B: (3CHjJ dJZQjO GdMeGFe aj GdaLQ hHQM Hj hLOj hRGjdfj UHQj s
(3BNQgG (B:s
(3Je GdcJGH JcGedJ fYe GdSQhQ dUGMHg hYaG GdEdg HLhOg hHaVdg Yf cGJHg s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B116 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B108s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B187 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs